Pengaruh tingkat bagi hasil terhadap Minat Masyarakat Menabung di Bank Syariah - Jihan Suwifania (Universitas Muhammadiyah Enrekang, 2022)
With the rapid growth of Islamic banks in Indonesia, several commercial banks have opened branches that also serve Muslims. This financial institution is not only experimenting with the expansion of Islamic banking in Indonesia; consumer demand for Shariah-compliant financial institutions is a much more significant driving force. Finally, a study is needed to determine the extent to which members of the public invest in Islamic Banks with a study entitled The Effect of Profit Sharing on Customer Interest in Savings in Islamic Banks. The research in this study uses a quantitative desk-based methodology. Information was collected with the help of a 14 item questionnaire, and results were evaluated using a Likert scale from 0 to 1, with additional tests performed for validity, reliability, and normality. Simple regression analysis and parametric tests were used to refute the null hypothesis.